Mykolas Firkovičius (1924–2000) and his work as a unique basis for the Karaim language revival - Firkavičiūtė, Karina (Vilnius University Proceedings, 2024)
This article presents the contribution of Mykolas Firkovičius (1924–2000) to the revival and continuation of the Karaim language through three strands of his activities: religion, poetry and the language itself. Mykolas Firkovičius was a native speaker of Karaim, Karaim community leader in Lithuania for many years and officially served a senior priest in 1993–2000. Among other works, he published texts in Karaim, sources, poetry compilations, prayerbooks, textbooks, and wrote himself in Karaim. He was a man that profoundly helped his nation to continue its cultural and linguistic life after disastrous times that interrupted Karaim legacy, changed and transformed it. He provided plenty of material to be used by those who want to survive as Karaims, to still speak the language, and to stay strong rooted in the traditions.
Keywords: Mykolas Firkovičius; Karaim; Karaim language; Karaim religion; Karaim poetry